Comprehensive factorization and I-central extensions - Bourn, Dominique (2012)
We show that, for a regular reflection functor I between efficiently regular categories, the reflection of an extension to an I-central extension is reduced to the comprehensive factorization of an explicit internal functor. We then analyse the Mal'tsev context where similar results are obtained under weaker conditions on I. (C) 2011 Elsevier B.V. All rights reserved.